Stigma associated with people living with HIV/AIDS in Mahwelereng, Limpopo Province - Tsebe, Koketjo Biggy (My University, 2016)
In this study, the researcher aimed to discover stigma associated with people living with HIV and AIDS in Mahwelereng, Limpopo province. The researcher sampled five males and five females and they were between the ages of 18 and 35. In-depth interviews were a method of choice during data collection. Thematic content analysis was used to analyse data. The results show negative perceptions towards PLWHA. The community discriminate PLWHA because of fear of being infected, with females being at a higher risk because they are perceived to be promiscuous. Participants also highlighted that black people lack knowledge of how to treat and behave towards HIV/AIDS infected individuals. It is recommended that there should be studies that focus on availability of interventions that aim to combat HIV/AIDS stigma. Lastly, the future studies should explore which race groups have more knowledge and perception about HIV and AIDS. KEY CONCEPTS: Acquired Immune Deficiency Syndrome; Human Immunodeficiency Virus; People Living with HIV and AIDS; Stigma.
Thesis (M. A. (Clinical Psychology)) -- University of Limpopo, 2016
Keywords: HIV/AIDS; HIV-positive persons -- South Africa -- Limpopo; HIV (Viruses); AIDS (Disease) -- Patients